Janaki in ’Ancient Promises" - A Victim of Family Honour - John Akkara, Merly (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Even educated women are reluctant to come to the main stream of society. What is holding them back? It’s nothing but the patriarchal society which is imposing too many dos and don’ts on them. It suffocates and thereby restrains them from coming forward to achieve their deserved status in the society. My humble attempt is to portray how false sense of family honour stands as an obstacle on the path of women empowerment.